IBU BEKERJA DENGAN PEMANFAATAN KELAS IBU HAMIL - Yusmaharani, Yusmaharani; Nurmaliza, Nurmaliza; Ratih, Rini Hariani (MIDWIFERY JOURNAL, 2021)
Backgound : The mortality rate of pregnant, maternity and postpartum women in Riau Province increased from the previous year. The Publich Health Office held a Maternity Class Program to broaden the knowledge of pregnant women. Purpose : of this study was to determine the relationship between work and the use of classes for pregnant women in Pekanbaru. Methode : This research is a quantitative analytic observational with the type of cross-sectional study design. The population in this study were all third trimester pregnant women in the work area of Harapan Raya Pekanbaru Publich Health Center in 2016 as many as 304. The sample was 211 people with a systematic random sampling technique. Collecting data using a questionnaire, previously the questionnaire has been tested for validity and reliability first to respondents with the same characteristics as many as 30 respondents. Data analysis was carried out univariate and bivariate using a computer program. Result : Bivariate analysis using Chi-square test with the estimated confidence interval (CI) or 95% confidence level CI. Univariate results found that most of the respondents did not use the class of pregnant women as many as 163 people (77%). The results of the Chi-Square Test show that the P-value of work on the use of the class of pregnant women is 0.008 (P<0.05) with an OR value of 3.565, which means that there is a relationship between work and class utilization of pregnant women. Conclusion : It can be concluded that there is a relationship between work and class utilization of pregnant women and working mothers are 3x at risk of not using the class of pregnant women compared to mothers who do not work.Suggestion for health workers to coordinate with pregnant women who work, so that the schedule for the implementation of the class for pregnant women can be mutually agreed so that the class for pregnant women can be attended by all pregnant women in their working area. And pregnant women can feel the benefits of attending classes for pregnant women.  Keywords : Job, Maternity Class ABSTRAK Latar Belakang : Angka kematian ibu hamil, bersalin dan nifas di provinsi Riau meningkat dari tahun sebelumnya. Dinas Kesehatan mengadakan Program Kelas Ibu Hamil untuk menambah wawasan ibu hamil.Tujuan : Untuk mengetahui hubungan pekerjaan dengan pemanfaatan kelas ibu hamil di pekanbaru.Metode : Penelitian ini bersifat kuantitatif analitik observasional dengan jenis desain  Cross-sectional Study. Populasi dalam penelitian ini adalah seluruh ibu hamil trimester III yang berada di wilayah kerja Puskesmas Harapan Raya Pekanbaru tahun 2016 sebanyak 304. Sampel sebanyak 211 orang dengan teknik pengambilan sampel secara Systematic Random Sampling. Pengumpulan data menggunakan kuesioner, sebelumnya kuesioner telah di lakukan uji validitas dan reabilitas terlebih dahulu kepada responden dengan karakteristik yang sama sebanyak 30 orang responden. Analisis data dilakukan secara  univariat dan bivariat dengan menggunakan program komputer.Hasil : Analisis bivariat menggunakan uji Chi-square dengan estimasi Confiden Interval (CI) atau tingkat kepercayaan 95% CI. Hasil univariat di dapatkan bahwa sebagian besar responden tidak memanfaatkan kelas ibu hamil sebanyak 163 orang (77%). Hasil Uji Chi-Square menunjukkan Pvalue pekerjaan terhadap pemanfaatan kelas ibu hamil adalah 0,008 (P<0,05) dengan nilai OR 3,565 yang artinya terdapat hubungan antara pekerjaan dan pemanfaatan kelas ibu hamil.Kesimpulan : Dapat disimpulkan bahwa terdapat hubungan antara pekerjaan dan pemanfaatan kelas ibu hamil dan ibu yang bekerja beresiko 3x tidak memanfaatkan kelas ibu hamil di bandingkan dengan ibu yang tidak bekerja.Saran bagi petugas Kesehatan untuk mengadakan koordinasi dengan ibu hamil yang bekerja, agar jadwal palaksanaan kelas ibu hamil dapat disepakati Bersama sehingga kelas ibu hamil bisa dihadiri oleh semua ibu hamil yang ada di wilayah kerjanya. Serta ibu hamil dapat merasakan manfaat mengikuti kelas ibu hamil.  Kata Kunci : Pekerjaan, Kelas Ibu Hamil